PyFuzzer：automatic in-memory fuzz testing method - Wei-ming LI; Jun-qing YU; Shao-bo AI (Tongxin xuebao)
Fuzz Testing is an effective method to mine all kinds of vulnerabilities.But the main drawbacks to current fuzz testing tools are:firstly,it produces high volume testing data and it’s extraordinary time consumption; secondly,if the accessing needs authentication,the greatest part of test data will be abandoned.PyFuzzer,a novel automatic in-memory fuzz testing tool combining static analysis,dynamic analysis and in-memory fuzz testing,was presented.The tool is highly automatic and effective.Compared with 4n FTP Fuzzer in testing WarFTPD and Serv-U,PyFuzzer can discover all vulnerabilities and improve test efficiency greatly.